Analyzing the Limitations of Agency and Rights in Migrant Women's Empowerment - Gilani, Syed Raza Shah; Al-Matrooshi, Ali Mohammed; Qureshi, Aisha Nayab (Pakistan Journal of Humanities and Social Sciences, 2023)
Migrant women constitute a substantial and heterogeneous cohort within the worldwide populace. Individuals depart from their nations of birth in pursuit of enhanced prospects, frequently encountering distinctive obstacles and susceptibilities during the course of their migratory expedition. The abstract notion of a "migrant woman" encompasses the range of experiences, rights, and challenges encountered by this heterogeneous cohort of women. The analysis explores the structural determinants that influence the process of migration among individuals, including economic inequalities, gender expectations, and governmental regulations pertaining to migration. Additionally, it draws attention to the various overlapping forms of discrimination that people experience and which depend on things like gender, race, socioeconomic status, and immigration status. Migrant women actively participate in various industries, encompassing both low-skilled and informal labour, domestic service, healthcare, and agricultural sectors. The labour and contributions of individuals have far-reaching global implications, exerting influence on the economies of both the countries from which they originate and the countries where they are received. Nevertheless, these individuals frequently encounter economic exploitation, precarious labour circumstances, and restricted availability of rights and social safeguards. To gain a comprehensive understanding of the abstract notion of migrant women, it is imperative to acknowledge the wide range of experiences they encounter and the ways in which their identities intersect. Addressing the systemic issues and inequalities faced by individuals requires a collective effort of global cooperation, collaboration, and dialogue. This article aims to shed light on the empowerment of migrant women and the insufficiency of agencies and rights in achieving this goal.